Pemberdayaan masyarakat Desa Sri Agung untuk meningkatkan ketahanan pangan dengan introduksi padi hitam di pekarangan - Made Deviani Duaja; Buhaira Buhaira; Nelyati Nelyati; Elis Kartika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
Now rice can be planted in the yard, using polybags and SRI Method (one seed per pot). Liquid organic fertilizer based on local microorganism (LOM) which is obtained by fermentation livestock urine and extract of golden snail. This extract is used as biodecomposer to ferment livestock waste into solid and liquid fertilizer. The fertilizer is used for black rice plant in polybag. This technology was applied in Sri Agung village from Sido Rukun and Sido Mukti area, specially for womens from several RT and for agriculture womens association that are active in the utilization of yard. The target is to increase the yield of the yard, previously no rice crops, now exist, at least each pot produced 500 g of dry black rice, 100 liters of liquid organic fertilizer per month and 50 kg of solid fertilizer per two months. The result showed, the level of PKK participation when mentoring is high because from 50 people, 40 people are present in every activity. Evaluation showed there are high farmer participation in land preparation and demonstration of RINMAS technology and low level farmers participation in implementation SRI method. It is recommended to planting rice on the yard.